Application of the Kwei Equation tomodel the T(g) Behavior of Binary Blends of Sugars and Salts - Weng, Lindong (2013)
Vitrification of sugar-based solutions plays an important role in cryopreservation, lyophilization, and the emerging field of anhydrous preservation. An understanding of the glass transition characteristics of such formulations is essential for determining an appropriate storage temperature to ensure an extended shelf life of vitrified products. To better understand the effect of salt son the glass transition temperature (T(g)) of glass-forming sugars, we investigated several data-fitting models (Fox, Gordon-Taylor and Kwei) for sugar-salt formulations using data from the literature, as well as new data generated on blends of trehalose and choline dihydrogen phosphate (CDHP). CDHP has recently been shown to have promise as a stabilizing agent for proteins and DNA. The Kwei equation, which has a specific parameter characterizing intermolecular interactions, provides good fits to the T(g) data for sugar-salt blends, and complements other commonly used models that are frequently used to model T(g) data.